The association between social capital indicators and psychological distress in Catalan adolescents - Carrillo-Alvarez, Elena; Andrés, Ana; Riera-Romaní, Jordi; Novak, Dario; Rodriguez-Monforte, Míriam; Costa-Tutusaus, Lluís; Guerra-Balic, Myriam (Frontiers in Psychology, 2022)
According to the WHO, globally, one in seven adolescents experiences a mental disorder, being in a detrimental situation towards educational achievement, social cohesion, future health and life chances. Calls to identify risk and resilience factors to develop effective preventive actions have been made. Following a systemic approach, we conducted a cross-sectional study on the relationship between social capital and psychological distress in a sample of Catalan adolescents in Barcelona, taking into account a range of other relevant aspects at different levels influencing mental health, including gender, age, migrant status, family background, lifestyle factors, body mass index, and self-rated health. Data was collected through validated questionnaires in December 2016 from 646 of 14 to 18 years-old adolescents from three public and private high schools in Barcelona (Spain). Data analysis included descriptive analysis, a correlational study and logistic regression to obtain the odds ratio for social capital indicators to be associated to psychological distress. Our results suggest that reporting higher levels of family support and higher levels of teacher-student trust reduce the likelihood of suffering psychological distress. Higher levels of neighborhood informal control were associated with mental health, but a possible detrimental effect cannot be ruled out. Being a girl, reporting low self-rated health or higher media use was also associated with higher likelihood of psychological distress. Current results may encourage interventions that focus on social capital as a means to reduce psychological distress and foster well-being in youth.